Measuring Areas on Large Scale Nautical Charts on Mercator-Secant - Vassallo, A.; Gargiulo, R. (The International Hydrographic Review, 2015)
This short paper presents a highly accurate module of surface deformation which permit to calculate, once and for all, the ellipsoid area corresponding to the area measured on nautical charts on Mercator-Secant. The accuracy of the measured surface increases together with the increase of the scale because it depends on the graphic error.